Interferon-α Subtypes As an Adjunct Therapeutic Approach for Human Immunodeficiency Virus Functional Cure - George, Jeffy; Mattapallil, Joseph J. (Frontiers in Immunology, 2018)
Human immunodeficiency virus (HIV) establishes life-long latency in infected individual. Though highly active anti-retroviral therapy (HAART) has had a significant impact on the course of HIV infection leading to a better long-term outcome, the pool of latent reservoir remains substantial even under HAART. Numerous approaches have been under development with the goal of eradicating the latent HIV reservoir though with limited success. Approaches that combine immune mediated control of HIV to activate both the innate and adaptive immune system under suppressive therapy along with “shock and kill’ drugs may lead to a better control of the reactivated virus. Interferon alpha (IFN-α) is an innate cytokine that has been shown to activate intracellular defenses capable of restricting and controlling HIV. IFN-α, however, harbors numerous functional subtypes that have been reported to display different binding affinities and potency. Recent studies have suggested that certain subtypes such as, IFN-α8 and IFN-α14 have potent anti-HIV activity with little or no immune activation whereas other subtypes such as IFN-α4, IFN-α5 and IFN-α14 activate NK cells. Could these subtypes be used in combination with other strategies to reduce the latent viral reservoir? Here we review the role of IFN-α subtypes in HIV infection and discuss the possibility that certain subtypes could be potential adjuncts to a “shock and kill” or therapeutic vaccination strategy leading to better control of the latent reservoir and subsequent functional cure.